Noise‐induced reduction in the attack rate of a planktivorous freshwater fish revealed by functional response analysis. (15th March 2019) - Hanache, Priscillia; Spataro, Thierry; Firmat, Cyril; Boyer, Nicolas; Fonseca, Paulo; Médoc, Vincent
Abstract: Anthropogenic noise can affect animals physically, physiologically, and behaviourally. Although individual responses to noise are well documented, the consequences in terms of community structure, species coexistence, and ecosystem functioning remain fairly unknown. The impact of noise on predation has received a growing interest and alterations in trophic links are observed when animals shift from foraging to stress‐related behaviours, are distracted by noise, or because of acoustic masking. However, the experimental procedures classically used to quantify predation do not inform on the potential demographic impact on prey. We derived the relationship between resource use and availability (the functional response) for European minnows ( Phoxinus phoxinus ) feeding on dipteran larvae ( Chaoborus sp.) under two noise conditions: ambient noise and ambient noise supplemented with motorboat noise. The shape and magnitude of the functional response are powerful indicators of population outcomes and predator–prey dynamics. We also recorded fish behaviour to explore some proximate determinants of altered predation. For both noise conditions, fish displayed a saturating (type II) functional response whose shape depends on two parameters: attack rate and handling time. Boat noise did not affect handling time but significantly reduced attack rate, resulting in a functional response curve of the same height but with a less steep initial slope. Fish exhibited a stress‐related response to noise including increased swimming distance, more social interactions, and altered spatial distribution. Our study shows the usefulness of the functional response approach to study the ecological impacts of noise and illustrates how the behavioural responses of predators to noise can modify the demographic pressure on prey. It also suggests that prey availability might mediate the negative effect of noise on predation. Community outcomes are expected if the reduced consumption of the main food sources goes with the overconsumption of alternative food sources, changing the distribution pattern of interaction strengths. Predation release could also trigger a trophic cascade, propagating the effect of noise to lower trophic levels.